Desenvolvimento de produto tipo barra com alto conteúdo proteico a base de torta parcialmente desengordurada da amêndoa de castanha de caju - Moreira, José Danrley (2024)
Partially defatted cake (TPD) is a by-product of processing cashew kernels to extract their oil. It has a high concentration of proteins and can therefore be used in the formulation of new products, helping to increase their nutritional value and their functional and technological properties. The aim of this study was to develop bars with a high protein content from the partially defatted cashew nut kernel cake. The bars were formulated with the addition of TPD, pea protein isolate, yacon concentrate (as a source of prebiotic oligosaccharides), glycerin, maltodextrin and cocoa butter, and subjected to physicochemical (centesimal composition) and nutritional analyses (determination of minerals, in vitro digestibility and amino acid profile). Sensory tests (acceptance and CATA and RATA descriptive tests) were carried out with three different audiences: the general public at Embrapa Agroindústria Tropical, students and staff at the Faculty of Physical Education at UFC - CE and physical activity practitioners at a private gym in Fortaleza-CE. The protein bar formulations achieved a significant protein content in their composition and can be claimed to have a high protein content according to current legislation, since they showed values higher than the minimum established (min. 20% protein). With regard to the sensory acceptance of the protein bars, it can be seen that in the first analysis comparing the different concentrations of yacon (5%, 10% and 15%), all the formulations showed good average acceptance in all attributes, except for aroma, which was in the average indecision zone 5 (neither liked nor disliked). In relation to the first CATA and RATA test, it was observed that the formulations had similar characteristics, with only the term “soft” showing a difference. In order to improve aroma acceptance, the second and third sensory tests were carried out with protein bars made with 10% yacon concentrate, in natural, vanilla or coffee flavors. All the formulations were accepted sensorially, and the vanilla flavored formulation stood out, with an average overall acceptance score of 7.1, corresponding to the “liked” category on the 9-point hedonic scale. The coffee-flavored formulation received the lowest score (5.8) in the taste attribute, although it achieved the highest value (7.0) in the aroma attribute. The second and third CATA tests showed significant differences between the formulations in most of the terms analyzed. The natural flavor bar with 10% yacon concentrate had an excellent amino acid profile, with the presence of all the essential amino acids in the quantities established by the legislation, presenting a complete amino acid profile. It also showed high in vitro protein digestibility. In terms of mineral characterization, the protein bar can be recognized as a source of zinc and magnesium, as well as having a high phosphorus and iron content. Finally, the high-protein bar made from the cashew kernel oil extraction cake not only contributes to the supply of a plant-based product, but also makes it a source of high-quality protein.